Caracterização dos usuários da atenção básica que manifestam vontade pela esterilização cirúrgica no município de São Carlos, São Paulo - Santos, Márcia Vieira Soares (2018)
Counseling in reproductive planning should consider the context of each person's life and the right of everyone to make decisions about reproduction in a free and informed way. The objective was to characterize primary care users who expressed their desire for surgical sterilization in the first year of implantation of the Line of Care of the Reproductive Planning for Surgical Sterilization of the city of São Carlos, São Paulo. It is an individual observational cross-sectional study involving 114 users from May 1, 2015 to April 30, 2016. The proportion of women (49.12%) and men (50.88%) was similar. The mean age of women was 32.9 years and that of men 34.8 years. Per capita income of up to half a minimum wage was associated with 4.7 times the preference for tubal ligation. The majority had between two to four live children (85.96%) and two to four children with current partner (a) (76.32%). The model of health care of origin of the users was indifferent. Around 50% of users were using an effective reversible contraceptive method. Most finished the process of reproductive planning in less than a year (60.53%), and three changed their opinion about the desired method. One switched from tubal ligation to vasectomy after completion of the procedure and two gave up tubal ligation preferring reversible contraceptive methods, one of which was after psychological evaluation and the other after social assessment. It is concluded that the age and number of live children met the legal criteria, that per capita family income up to half a minimum wage was associated with the preference for tubal ligation and that the rate of change of the type of surgical sterilization during the process of reproductive planning was low.